KNOWLEDGE MANAGEMENT SYSTEM DEVELOPMENT TO IMPROVE CUSTOMER SERVICE QUALITY ON A CAKE SHOP - Faroqie, Haveiszal; Mey Jesika Rani, Monica; Nurwegiono, Muhammad (Kurawal - Jurnal Teknologi, Informasi dan Industri, 2025)
This study aims to develop a WordPress-based Knowledge Management System (KMS) to enhance customer service quality at "PUKIS CIKME" shop. The knowledge transformation process utilizes the SECI (Socialization, Externalization, Combination, Internalization) method, mapping tacit and explicit knowledge flows within the organization. The system is designed to simplify information management, support employee collaboration, and provide a formal two-way feedback channel between employees and management. The KMS development follows partial KMSLC (Knowledge Management System Life Cycle) stages, including knowledge capture, blueprint design, and system verification. The result is a WordPress-based system that is flexible, user-friendly, and adaptable to business needs. This system enables improved operational efficiency, employee innovation, and responsiveness to customer needs. Thus, implementing the KMS significantly contributes to enhancing the shop's productivity and sustainability.